Epistemological foundations of complexity in curricular design in initial teacher training - Portocarrero-Gutierrez, César A. (2023)
The objective of this research has been to analyze the National Curriculum Design (DCN) of Secondary education of Initial Teacher Training (FID) from the perspective of the complexity of Morin's theory; The foundations of complex thinking were analyzed based on the theory of Morín and some authors who look at complex thinking as the phenomenon of a new posture of knowledge. It has also been possible to analyze complex thinking in the domains and competencies of the graduation profile and complex thinking in the transversal approaches in the FID. The methodology that has been used is the review of literature that has allowed us to answer the questions in reference to complex thinking, which is evidenced by various sources of information such as articles, books and information, resulting in evidence of the foundations of complexity. in the DCN of the FID, evident in its domains, competencies and epistemological foundations. The conclusions of the study confirm the presence of epistemological foundations of complexity in the curricular design of initial teacher training. They highlight the importance of effectively implementing complex thinking in teacher training centers through enriching pedagogical strategies.